A WhatsApp-based Flipped Classroom Model: Effect on Students’ Higher Order Thinking Skill - Fauzi Muharom; Arif Nugroho; Heldy Ramadhan Putra P; Giswa Aria Nanda (Ta'dib: Jurnal Pendidikan Islam, 2022)
This study casts the light on the effect of WhatsApp-based flipped learning on students’ higher order thinking skills (HOTS). This study was experimental research involving 68 university students majoring in Islamic education at UIN Raden Mas Said Surakarta Indonesia who were divided into experimental group (N=34) and control group (N=34). A set of pre- and post-tests were used to measure the students’ HOTS. The data were analyzed through an independent sample t-test using SPSS version 24. The results showed that the students of experimental group successfully outperformed their counterparts in the post-test (p-value 0.000 < 0.05). Also, the result of independent t-test revealed a significant difference between the scores of pre- and post-test of the experimental students. WhatsApp-based flipped learning is a promising model for enhancing the students’ HOTS, as well as improving the efficacy of teaching-learning process. These results provide fruitful insights for higher educational stakeholders (teachers, students, and policymakers) to begin acknowledging flipped classroom model as an alternative approach for teaching in university level.